ADHD, depression, and substance abuse risk among beginning college students. Issue 1 (2nd January 2020) - Mochrie, Kirk D.; Whited, Mathew C.; Cellucci, Tony; Freeman, Taylor; Corson, Ansley Taylor
Abstract: Objective: This study examined differences in substance use, depression, and academic functioning among ADHD and non-ADHD college students. Participants: Included 1, 748 students (ages 18–25; women 68.4%; Caucasian 71.3%) with and without history of ADHD. Methods: We assessed the relationship of ADHD to substance use variables, controlling for depressive symptoms and examined relationships with GPA. Results: ADHD students were more likely to have engaged in frequent alcohol use, binge drinking, regular marijuana use and to have used other drugs in the last year. They reported higher depression symptoms than non-ADHD students, although substance abuse risk remained high even when controlling for depressive symptoms. ADHD students had lower overall GPA than those without ADHD. However, this difference was no longer significant when controlling for depression and marijuana use. Conclusions: College campuses should consider programing aimed at identifying ADHD students at risk for developing substance abuse problems and emotional difficulties.